PEMBUATAN TAPE TALAS (Colocasia esculenta) BERDASARKAN LAMA FERMENTASI SEBAGAI RANCANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI DI SMA - Siregar, Anna Sherley; ', Darmawati; Mahadi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research was conducted to determine fermented tape taro (Colocasia esculenta) by fermentation in April and May 2016. The results are used to design Student Worksheet (LKS) Biology in senior high school on Conventional Biotechnology concept. This research was carried out by two phases: experimental and LKS design stage. The experimental research carried out by using a completely randomized design (CRD), which consists of 6 treatments and 3 replicates in order to obtain 18 units of the experimental design. The observed data for each parameter, were analyzed using analysis of variance (ANOVA). If there are differences among the treatments there will be a further test Duncan's Multiple Range Test (DMRT) at 5% level. The parameters observed reduction sugar, alcohol content, pH, water content, and organoleptic texture, color, aroma and flavor. The results showed that the length of fermentation significant effect on reducing sugar, alcohol content, pH, water content, and organoleptic texture, color, flavor and taste tape taro (Colocasia esculenta). Fermentation time of 60 hours is a long time the best fermentation produces organoleptic texture, color, aroma and flavor. Which results in reducing sugar by 10.73%, 0.90% alcohol content, pH 3.82, and the water content of 74.29%. The results of the research could be used as design Student Worksheet (LKS) Biology in senior high school.Keywords: Tape Taro, Time Fermentation, Student Worksheet (LKS)